2021
DOI: 10.1007/s11684-021-0854-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and risk factors of COVID-19 patients with chronic hepatitis B: a multi-center retrospective cohort study

Abstract: The Coronavirus disease 2019 (COVID-19) has spread globally. Although mixed liver impairment has been reported in COVID-19 patients, the association of liver injury caused by specific subtype especially chronic hepatitis B (CHB) with COVID-19 has not been elucidated. In this multi-center, retrospective, and observational cohort study, 109 CHB and 327 non-CHB patients with COVID-19 were propensity score matched at an approximate ratio of 3:1 on the basis of age, sex, and comorbidities. Demographic characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…According to (Huang et al, 2020), who stated that 98% of the infected patients experienced fever followed by cough (76%), dyspnea (55%) and loss of taste or smell, symptoms can include fever. The results corroborate with those of Wang et al (2022) who discovered that diarrhoea was present in 34.0% of cases. Although Covid-19 has a number of mechanisms that can produce symptoms, the one that causes headaches is still unknown.…”
Section: Sars-cov-2supporting
confidence: 91%
“…According to (Huang et al, 2020), who stated that 98% of the infected patients experienced fever followed by cough (76%), dyspnea (55%) and loss of taste or smell, symptoms can include fever. The results corroborate with those of Wang et al (2022) who discovered that diarrhoea was present in 34.0% of cases. Although Covid-19 has a number of mechanisms that can produce symptoms, the one that causes headaches is still unknown.…”
Section: Sars-cov-2supporting
confidence: 91%
“…Patients with liver diseases may have a greater risk of worse outcome from COVID-19 than the general population. [1][2][3] Currently, there are about 292 million people worldwide infected with HBV and 86 million in China alone. 4 Vaccination is an effective intervention in preventing SARS-CoV-2 infection, severe symptom and death.…”
Section: Introductionmentioning
confidence: 99%
“…COVID‐19 caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has emerged as a major burden worldwide, resulting in serious public health challenges. Patients with liver diseases may have a greater risk of worse outcome from COVID‐19 than the general population 1‐3 . Currently, there are about 292 million people worldwide infected with HBV and 86 million in China alone 4 …”
Section: Introductionmentioning
confidence: 99%
“…Only one of their patients developed severe COVID-19, thus they suggested that CHB does not affect the outcome of COVID-19. In contrast, a recent study by Wang et al [ 60 ] included 109 patients with CHB and 327 patients without HBV infection, and reported that patients with CHB were more likely to develop severe COVID-19 disease (27.5% vs 5.2%, respectively) with higher mortality. They have reported that factors affecting COVID-19 severity in patients with CHB include elevated total bilirubin, ALP, AST, ALT, LDH and D-dimer and decreased serum albumin and albumin to globulin ratio[ 60 ].…”
Section: Patients With Viral Hepatitis and Covid-19mentioning
confidence: 97%